1990
DOI: 10.1021/jm00171a040
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of .alpha.-[[(2-haloethyl)amino]methyl]-2-nitro-1H-imidazole-1-ethanols as prodrugs of .alpha.-[(1-aziridinyl)methyl]-2-nitro-1H-imidazole-1-ethanol (RSU-1069) and its analogs which are radiosensitizers and bioreductively activated cytotoxins

Abstract: alpha-[(1-Aziridinyl)methyl]-2-nitro-1H-imidazole-1-ethanols, of general formula ImCH2CH(OH)CH2NCR1R2CR3R4, where Im = 2-nitroimidazole and R1, R2, R3, R4 = H, Me, are radiosensitizers and selective bioreductively activated cytotoxins toward hypoxic tumor cells in vitro and in vivo. Treatment of the aziridines with hydrogen halide in acetone or aqueous acetone gave the corresponding 2-haloethylamines of general formula ImCH2CH(OH)CH2(+)-NH2CR1R2CR3R4X X-, where R1, R2, R3, R4 = H, Me, and X = F, Cl, Br, I. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 4 publications
1
38
0
Order By: Relevance
“…GFP/R9 and GFP5 cells grown as xenografts were allowed to reach exponential growth (Figure 3, tumour doubling time of approximately 4 days) before combined treatment with radiotherapy and RB6145 -a chemical precursor of RSU1069 that exhibits reduced systemic toxicity in vivo. 22 This allowed us to evaluate the ability of our therapeutic approach to potentiate the radioresponse of an established tumour with a clinically relevant hypoxic fraction. 24 Consistent with our in vitro data, hypoxia-regulated P450R expression proved a successful approach to enhance bioreductive hypoxic cell cytotoxicity and hence improve the efficacy of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GFP/R9 and GFP5 cells grown as xenografts were allowed to reach exponential growth (Figure 3, tumour doubling time of approximately 4 days) before combined treatment with radiotherapy and RB6145 -a chemical precursor of RSU1069 that exhibits reduced systemic toxicity in vivo. 22 This allowed us to evaluate the ability of our therapeutic approach to potentiate the radioresponse of an established tumour with a clinically relevant hypoxic fraction. 24 Consistent with our in vitro data, hypoxia-regulated P450R expression proved a successful approach to enhance bioreductive hypoxic cell cytotoxicity and hence improve the efficacy of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…For these studies, the prodrug RB6145 (1-[3-(2-bromoethylamino)-2-hydroxypropyl]-2-nitroimidazole) was used, which when hydrolysed in vivo releases RSU1069. 22 As highlighted above, RSU1069 shows preferential toxicity towards hypoxic cells. Radiotherapy was chosen to control the oxic cell population within the tumours.…”
Section: Hypoxia-driven Human Cytochrome C P450 Reductase Expression mentioning
confidence: 91%
See 1 more Smart Citation
“…RB6145 is completely converted to its active product RSU1069 within minutes of administration in vivo (Jenkins et al, 1990), and the plasma half-life of RSU1069 is about 20 min in C3H mice (Walton and Workman, 1988;Binger and Workman, 1990). It is thought that RSU1069 would reach its maximum tumour concentration within 15 min of administration, hence any interference with tumour blood supply thereafter would not only create hypoxia but also prevent efflux of the drug from the tumour, thereby enhancing tumour toxicity (Bremner et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a prodrug of RSU1069 has been prepared and licensed to the pharmaceutical industry for clinical development. This drug, RB6145 (Jenkins et al, 1990), has also been shown to have considerable anti-tumour activity when combined with treatments that increase the level of tumour hypoxia (Bremner 1993;Stratford et al, 1994). Thus, in view of the findings on induction of hypoxia in murine tumours after the inhibition of NOS activity, experiments were carried out in which RB6145 was combined with nitro-L-arginine (Wood et al, 1994a).…”
mentioning
confidence: 99%